2018
DOI: 10.1080/02619768.2018.1426566
|View full text |Cite
|
Sign up to set email alerts
|

‘I will do it but religion is a very personal thing’: teacher education applicants’ attitudes towards teaching religion in Ireland

Abstract: There has been extensive research internationally describing teachers' homogenous socio-demographic backgrounds and critiquing the associated equity and diversity issues, most especially with regard to ethnicity and gender, and to a lesser extent, social class and disability. Yet, teachers' religious affiliations and/or convictions have rarely been explored. Since ninety-six per cent of state primary schools in Ireland are denominational, considering religious diversity in teaching is both critically important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
(23 reference statements)
0
13
0
Order By: Relevance
“…Qualitative data were analysed thematically, grouping similar descriptions (for example attitudes towards teaching religion, main reasons for choosing a teaching career) into categories (Heinz, Davison, and Keane 2018;Keane and Heinz 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative data were analysed thematically, grouping similar descriptions (for example attitudes towards teaching religion, main reasons for choosing a teaching career) into categories (Heinz, Davison, and Keane 2018;Keane and Heinz 2016).…”
Section: Methodsmentioning
confidence: 99%
“…DITE explores compositions of primary and post-primary teacher education applicants and entrants across state-funded initial teacher education (ITE) providers in Ireland. To date, the project team has examined the participation, career motivations and experiences of various under-represented groups, including people from minority ethnic Heinz 2015, 2016) and/or minorityreligious (Heinz, Davison, and Keane 2018) and/or lower socio-economic backgrounds (Heinz, Keane, and Foley 2017;Lynch 2018, 2020), people with disabilities (Keane, Heinz, and Eaton 2018) and/or members of the LGBTQ+ community (Heinz, Keane, and Davison 2017). Analyses have confirmed the homogeneity of the Irish teaching body which has been predominantly White, Irish, and female, with significant under-representation from a range of minority and/or socially disadvantaged groups.…”
Section: Introductionmentioning
confidence: 99%
“…In some education systems, teachers who work at denominational schools are strictly required to adhere to the school's religious principles; otherwise, they can be dismissed as their opinions might contradict the school's ethos (Heinz et al 2018). On the other hand, the question is whether one's religious faith or the lack of it-or any other conviction-should surface in class and whether it influences the teaching process.…”
Section: Introductionmentioning
confidence: 99%
“…26% of young people in this age group say they never attend a religious service (7). A study by Heinz et al (2018) also found low levels of religious practice and religiosity among young people in Ireland. Since at least the beginning of this millennium, adolescents in England who regularly attend and participate in religious activities are minority among their peers (Kay and Francis, 2001).…”
Section: The Other Side Of Wellbeing and Identitymentioning
confidence: 96%